Pengaruh Customer Relationship Management (CRM) Terhadap Loyalitas Pelanggan Pada Apotek Mega Mulia - Ali Ibrahim; Tanti Hidayah; Alisia Silver Stone; Yona Saymona; Tea Anggelah; Siti Raisah Adilah (STMIK Budi Darma, 2021)
In order to increase consumers, the pharmacy strategy is to provide services that match their needs and protect good ties with customers so that customer loyalty will be formed. To analyze the influence of aspects of customer identification, customer differentiation, budget interaction, and customization on customer loyalty at Apotek Mega Mulia is the aim of this research. Quantitative description with survey approach is the type of research in this research. The non-random method with accidental sampling was chosen by the researcher as a method of collecting information. Multiple liner is the analysis used. Based on the results of the information analysis, the data obtained by the value of Fcount 17.084 > Ftable 2.45. This shows that customer loyalty is significantly influenced by all factors. Of these four aspects, the calculated value for the customer differentiation aspect is 3,213 which is very large compared to the calculated value for the customer identification aspect of 2,283, customer interaction is 2,765, and customization is 2,226. The conclusion is that the aspects of Customer Relationship Management (CRM) are customer identification, customer differentiation, customer interaction, customization which together have a significant impact on customer loyalty at Mega Mulia pharmacies